Coupling of Cutoff Modes in a Chain of Nonlinear Metallic Nanorods - 崔维娜 李红霞 孙敏 朱永元 (Chinese physics letters, 2016)
We study the coupling of cutoff modes in a chain of metallic nanorods embedded in a Kerr nonlinear optical medium with strong near-field interactions analytically. Based on a quasidiscreteness approach, we derive a system of two coupled nonlinear Schrbdinger equations governing the evolution of the envelopes of these modes. It is shown that this system supports a variety of subwavelength plasmonic lattice vector solitons of the bright- bright, bright-dark, dark-bright, and dark-dark type through a cross-phase modulation. It is also shown that the existence of different solitons depends strongly on the gap width scaled for the rod radius and the type of nonlinearity of the embedded medium.